The threat to South African water security posed by wastewater-driven eutrophication: a proposal for a new regulatory approach - Harding, William Russell (Institute of Marine and Environmental Law, 2017)
The quality of South Africa's raw potable water resources is severely impacted by eutrophication (nutrient enrichment). As much as two-thirds of the reservoir impounded resource may be affected. Wastewater effluents and/or the integration of wastewater return flows as part of the water balances of many reservoirs constitute the primary source of this nutrient pollution. South Africa's historical awareness and understanding of the eutrophication threat to surface waters is comparable with that of other, similarly-afflicted, countries. In particular, the need to manage phosphorus was recognised as early as 1962 when South Africa promulgated one of the first (global) regulations for phosphorus in wastewater effluents. More recently, eutrophication has been ranked as a high priority by the the National Water Resource Strategy. Despite this background, phosphorus removal from wastewater effluents in South Africa remains virtually unregulated. Additionally, there is no resource-directed protocol for the accounting of all sources of phosphorus (or other pollutants) at a catchment level, rendering problematic, if not impossible, the fair and equitable allocation of levies on wastewater discharges. This dissertation examines how wastewater-originating eutrophication is regulated in the USA and Europe, with phosphorus as a central focus. A comparative assessment of the equivalent situation in South Africa is provided and the shortcomings of the latter highlighted. As a solution, I suggest an equitable and transparent scheme of pollutant accounting by individual source, ideally suited to the allocation of waste discharge levies. Applied against a specific resource requirement, for example an identified need to reduce phosphorus in a particular reservoir, this approach also provides a legally sound scheme for pollutant load regulation and permitting.